Fluorescent Detection of Trace Water in Methanol Based on an Al(III) Chemical Sensor. Issue 11 (12th September 2016) - Hao, Liang; Qiu, Qi‐ming; Wang, Wen‐jie; Gu, Leilei; Li, Hui
Abstract: A colorimetric and fluorescent sensor for trace water in methanol has been designed and characterized, which is a kind of aluminium‐Schiff base coordination complex derived from diaminomaleonitrile. The fluorescence properties of this complex have been studied based on excited state intramolecular proton transfer (ESIPT) and intramolecular charge transfer (ICT) mechanism. The fluorescent emission of Al‐L complex can be quenched by 0.1% water and distinguished by naked eyes. The detection limitation is 0.01% recognized by fluorescence spectra. Abstract : A colorimetric and fluorescent sensor for trace water in methanol has been designed and characterized, which is a kind of aluminium‐Schiff base coordination complex derived from diaminomaleonitrile. The fluorescence properties of this complex have been studied based on excited state intramolecular proton transfer (ESIPT) and intramolecular charge transfer (ICT) mechanism. The fluorescent emission of Al‐L complex can be quenched by 0.1% water and distinguished by naked eyes. The detection limitation is 0.01% recognized by fluorescence spectra.